2021
DOI: 10.2215/cjn.05920421
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Acute Kidney Injury with Oral Anticoagulants in Elderly Adults with Atrial Fibrillation

Abstract: Background: Anticoagulation with either with a vitamin K antagonist or a direct oral anticoagulant (DOAC) may be associated with acute kidney injury (AKI). Our objective was to assess the risk of AKI among elderly individuals with atrial fibrillation (AF) newly prescribed a DOAC (dabigatran, rivaroxaban, or apixaban) versus warfarin. Methods: A population-based cohort study of 20,683 outpatients in Ontario, Canada, ≥66 years, with atrial fibrillation who were prescribed warfarin, dabigatran, rivaroxaban or ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 47 publications
6
19
0
Order By: Relevance
“…warfarin. [23] Consistent with most other studies,[9, 12, 21, 23] our results did not infer any materially different effect between patients with baseline CKD and those without CKD. It is noteworthy that the AKI incidence rates in our study were much lower than those reported by Yao et al in their United Stated claims database study where AKI was based on primary and secondary diagnoses of AKI in linked hospitalisation data.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…warfarin. [23] Consistent with most other studies,[9, 12, 21, 23] our results did not infer any materially different effect between patients with baseline CKD and those without CKD. It is noteworthy that the AKI incidence rates in our study were much lower than those reported by Yao et al in their United Stated claims database study where AKI was based on primary and secondary diagnoses of AKI in linked hospitalisation data.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings, using the Aberdeen algorithm case ascertainment method, are consistent with several previous studies on this topic, among patients with NVAF using rivaroxaban compared with those using warfarin [9,10,12,21] or phenprocoumon, [11] including among high risk groups such those with CKD [11,12,22], diabetes, [9,12], heart failure [9] or the elderly. [9,10,21] Some have also shown similar effect sizes (15-19% reduced AKI risk), although some have reported a larger, ~30% lower risk with rivaroxaban [9,22] vs. warfarin, including with an even larger ~50% lower risk seen in one study. [22] Furthermore, a recent large meta-analysis of data from randomised controlled trials (RCTs) and observational studies reported a 30% reduced risk of AKI among users of DOACs vs. warfarin.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“… 48 , 49 In a Canadian population-based cohort study in >20,000 elderly adults with atrial fibrillation, the use of DOACs (dabigatran, rivaroxaban, apixaban) was associated with a significantly lower risk of AKI compared with warfarin, and the risk was consistent across each eGFR strata. 50 The latter suggest that the use of DOACs in patients with multiple risk factors for developing ARN may be an attractive preventive strategy. In addition, it is important to note that approximately 20% of our patients had significant microhematuria several months before the AKI event, advocating that urinary sediment should be closely monitored in those patients with risk factors for ARN in whom anticoagulant therapy is initiated.…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for in-hospital AKI in this population were age (per 10-year increase), the use of diuretics before admission, and baseline hemoglobin (per 20 g/L decrease). Moreover, Harel et al [45] in a very recent population-based cohort study of 20,683 outpatients in Ontario (Canada) assessed the risk of AKI among elderly individuals (more than 66 years old) with atrial fibrillation newly prescribed a DOAC (dabigatran, rivaroxaban, or apixaban) versus warfarin. They postulated several mechanisms for anticoagulant-induced AKI such as: systemic bleeding leading to hypotension, acute interstitial nephritis, and anticoagulant related nephropathy, a condition mediated by glomerular hemorrhage leading to the formation of obstructive red cell casts in distal tubules and free radical injury from lysed red blood cells particularly at supratherapeutic level of anticoagulation [46,47].…”
Section: Discussionmentioning
confidence: 99%